Campur Kode Dan Alih Kode Dalam Novel Milea Suara Dari Dilan Karya Pidi Baiq - Malihatuz Zuhriyah Istianti; Mukhlis Mukhlis; HR Utami (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The research entitled "Code Mixing and Code Switching in the Novel Milea Suara dari Dilan by Pidi Baiq" aims to describe the types of code mixing and code switching in the novel Milea Suara dari Dilan with the data source being the novel Milea Suara dari Dilan by Pidi Baiq. To find the research data, documentation techniques were used. Apart from that, to analyze the research data, content analysis techniques were used. The results found contained 77 pieces of data including, 54 code-mixing in the form of words, 5 code-mixing in the form of phrases, 3 code-mixing in the form of clauses, 1 code-mixing in the form of basters, 11 internal code-switching and 3 external code-switching.